Readiness for Online Learning, Social Media Assignment, and Its Effects on Learning Motivation of Islamic Education (PAI )Students - Amet Amet; Yuli Marlina; Supiana Supiana; Qiqi Yuliati Zaqiah (STAI Miftahul Ula Nganjuk, 2023)
This study examines the extent to which online learning preparation has been implemented despite the pandemic's termination. Even said, some campuses still offer face-to-face instruction with the remaining 30% of instruction taking place online. Based on this, the researcher seeks to ascertain the viability of social media-based online assignments and learning, as well as their impact on student motivation. To determine the link between variable constructions, this study employs the SmartPls path data analysis technique. All PAI students at the Islamic University of Jakarta made up the sample, which included 56 respondents, of which 20 were men and 36 were women. The study's findings showed a 37.8% boost in learning motivation for those who were prepared for online learning. Additionally, there is a 53% boost in learning motivation for tasks while using social media. It is clear that technology and education will always go hand in hand, and that it will always be a flexible instrument for learning.